Chinese contract law : civil and common law perspectives - DiMatteo, Larry A.; Chen, Lei (Lawyer) (Cambridge : Cambridge University Press, 2018)
This book is the product of a unique collaboration between Mainland Chinese scholars and scholars from the civil, common, and mixed jurisdiction legal traditions. It begins by placing the current Chinese Contract Law (CCL) in the context of an evolutionary process accelerated during China's transition to a market economy. It is structured around the core areas of contract law, anticipatory repudiation (common law) and defense of security (German law); and remedies and damages, with a focus on the availability of specific performance in Chinese law. The book also offers a useful comparison between the CCL and the UNIDROIT Principles of International Commercial Contracts, as well as the Convention on Contracts for the International Sale of Goods. The analysis in the book is undertaken at two levels - practical application of the CCL and scholarly commentary.
History of chinese contract law / Chen Lei & Larry A. Dimatteo -- General principles under the CCL / Han Shiyuan -- General principles of Chinese contract law : an English common law perspective / Christian Twigg-Flesner -- Good faith in contract performance in Chinese and common laws / Ewan McKendrick & Qaio Liu -- General principles of Chinese contract law : a Scottish perspective / Martin Hogg -- Liability prior to contract formation in Chinese contract law / Shen Wei -- Pre-contractual liability from a civil lawyer's perspective / Barbara Passa -- Pre-contractual liability through the looking glass of the common law / Alexander Loke -- Prospect of validity in Chinese contract law / Wang Yi -- Invalidity of contract in Chinese and English contract law / Mindy Chen-Wishart -- Impossibility of performance and contract validity : a German law perspective / Lutz-Christian Wolff -- Perspectives on Chinese contract law : performance and breach / Ding Chunyan -- Anticipating breach, change of circumstances, and third party rights : a civil law perspective / Ulrich Schroeter -- Chinese law of performance and breach : a common law perspective / James Devenney & Geraint Howells -- Damages and specific performance in Chinese contract law / Chen Lei -- Chinese contract law on remedies and damages : a civil law perspective / Michel Cannarsa -- Debt instead of damages in the common law / Michael Bridge -- CCL and and unidroit principles / Andre Janssen & Samuel C.K. Chau -- CCL and CISG : a comparative analysis of formation, performance, and breach / Larry Dimatteo & Jingen Wang.
Title from publisher's bibliographic system (viewed on 24 Oct 2017).
Keywords: Contracts -- China; Performance (Law) -- China; Contracts